Cognitive Status Correlates with CXCL10/IP-10 Levels in Parkinson’s Disease - Natália Pessoa Rocha; Paula Luciana Scalzo; Izabela Guimarães Barbosa; Mariana Soares Souza; Isabela Boechat Morato; Érica Leandro Marciano Vieira; Paulo Pereira Christo; Antônio Lúcio Teixeira; Helton José Reis (Parkinson's Disease)
Cognitive impairment and depressive symptoms are of great interest in Parkinson’s disease (PD), since they are very common and lead to increased disability with poor quality of life. Inflammatory mechanisms have been implicated in PD and its nonmotor symptoms. In the current pilot study, we aimed to evaluate plasma levels of chemokines in PD patients and to analyze the putative association of chemokines with depressive symptoms and cognitive performance. We hypothesized that higher chemokines levels are associated with worse cognitive performance and increased depressive symptoms in PD. For this purpose, 40 PD patients and 25 age- and gender-matched controls were subjected to a clinical evaluation including cognitive and mood tests. Peripheral blood was drawn and plasma levels of CCL2/MCP-1, CCL11/eotaxin, CCL24/eotaxin-2, and CXCL10/IP-10 were measured by enzyme-linked immunosorbent assay. PD patients and control individuals presented comparable plasma concentrations of all the evaluated chemokines. In PD patients, CXCL10/IP-10 plasma levels correlated positively with Hoehn and Yahr staging scale. In addition, the higher CXCL10/IP-10 levels, the worse performance on cognitive tests. Although there was no significant difference between PD patients and control individuals regarding chemokines levels, our preliminary results showed that CXCL10/IP-10 may be associated with cognitive status in PD.